Empowering Communities through Eco-Creative Business: A Case Study of Ichinogami - Eriya Wiguna, Syahrul; Eria Azola Siregar, Arafahni; Nursyamsita Yanuarini, Annisa; Ayu Pratami, Putri; Sjarief Sjaiful Nazli, Rizal (SocioHumania: Journal of Social Humanities Studies, 2025)
This study examines the sustainable business strategies of Ichinogami, a creative MSME based in Jakarta, Indonesia, that specializes in environmentally friendly papercraft. Using a qualitative case study approach, this research explores how Ichinogami aligns its practices with the principles of the green economy and circular economy, contributing to the national agenda for sustainable MSMEs. The findings reveal that Ichinogami integrates eco-certified materials, digital innovation, and a cradle-to-cradle product design model that promotes waste reduction and material reuse. Additionally, the company employs an inclusive business model that emphasizes community empowerment, education, and cultural promotion through creative workshops and community-based marketing. Ichinogami’s strategic use of digital platforms and multi-channel distribution has also allowed it to maintain relevance in a competitive market while fostering customer loyalty and environmental awareness. The research highlights Ichinogami's role in promoting low-carbon entrepreneurship and its ability to scale environmental impact through product innovation and community collaboration. The study concludes that Ichinogami is a model for sustainable microenterprise development, though it must continue to address challenges such as limited production capacity and international market penetration.